The incidence of esophageal cancer in patients with Asian Glow (Research, Society and Development, 2022)
A deficiency of ALDH2 generates excess acetaldehyde, detecting signs and symptoms of facial flushing, also known as Asian Glow or Facial Flushing Syndrome. It is accompanied by nausea and headache, being considered a possible protective factor against alcoholism due to the clinical condition. This review aims to evaluate the relationship of Asian Glow with Esophageal Cancer and its influencing factors in the incidence of Asian pollution. A systematic review of the literature with free electronic access in the databases PubMed, Ministry of Health and Virtual Health Library (VHL), with a total number of 9 articles selected in the English language, filtering the articles related to the Asian cancer correlation. Applications for inclusion of publications of scientific articles in the period between 2009 and 2019. We conclude that the increase in alcohol consumption worldwide is directly related to a higher incidence of cancer in the world, especially in East Asian countries where a percentage of individuals with ALDH2 deficiency is high. Analyzing all four main points: the polymorphism of the genes encoding ALDH2, the Asian brightness, a tolerance to the manifestation of flushing and esophageal cancer (EC) we can reach a final result. EC is unrelated to Asian Glow, but it can cause ALDH2 which causes some patients with this syndrome.